2005
DOI: 10.1016/j.amjhyper.2004.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin-6 gene G-174C polymorphism and plasma plasminogen activator inhibitor-1 level in Chinese patients with and without hypertension

Abstract: The present study showed a positive association of the IL-6 GG genotype with hypertension and with elevated plasma PAI-1 level in normotensive individuals in a Chinese population in Taiwan. Our findings suggest that the IL-6 gene promoter G-174C polymorphism may affect the regulation of PAI-1 and blood pressure through an inflammatory mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The IL6 *C allele was associated with elevated blood pressure in dialysis patients (Losito et al 2003). Chinese hypertensive patients, in contrast with Caucasians, were found to have an increased number of -174*G/*G homozygotes compared with normotensive subjects (Jeng et al 2005). This finding suggests that ethnicity along with gender-dependent factors might influence the effect of genetic polymorphism on interleukin expression.…”
Section: Discussionmentioning
confidence: 95%
“…The IL6 *C allele was associated with elevated blood pressure in dialysis patients (Losito et al 2003). Chinese hypertensive patients, in contrast with Caucasians, were found to have an increased number of -174*G/*G homozygotes compared with normotensive subjects (Jeng et al 2005). This finding suggests that ethnicity along with gender-dependent factors might influence the effect of genetic polymorphism on interleukin expression.…”
Section: Discussionmentioning
confidence: 95%
“…Given the close association of adiponectin and PAI-1, it was not surprising to observe an impact of adiponectin T94G genotype on plasma PAI-1 levels. This genotype effect might be mediated indirectly through its influence on adiponectin production, or it could be in linkage disequilibrium with some functional/etiological variants on the adiponectin gene locus like the examples of PAI-1 4G/5G polymorphism [23 ]or IL-6-174 polymorphism [24], that may affect plasma PAI-1 levels. Obviously, it would not suffice to state for a direct, causal relationship between adiponectin genotype and plasma PAI-1 since this is only a cross-sectional survey in a particular population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the possible association of this genotype with plasma PAI-1 had not been reported yet. Our previous studies [21,22,23,24]had shown correlations of elevated plasma PAI-1 to insulin resistance, dyslipidemia, hypertension, PAI-1 promoter 4G/4G and interleukine-6 (IL-6) –174GG genotype but not to angiotensin-I converting enzyme DD genotype. In this study, the adiponectin genotype and the plasma levels of adiponetcin and PAI-1 were determined in patients with and without hypertension to explore the interrelationships of G94T genotype, plasma adiponectin, PAI-1, and blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…19,29 Given the role of IL-6 as a key mediator of acute phase reaction, single nucleotide polymorphisms (SNPs) in the IL-6 gene (IL6) have gained much attention, and a number of SNPs in the IL-6 gene promoter have been found to be related to the concentrations of acute phase proteins. [30][31][32][33][34] The IL-6 gene À174G4C polymorphism has been associated with PAI-l level in patients with or without hypertension, 30 and À174GG genotype has been associated with lower IL-6 levels after coronary artery bypass grafting (CABG) 31 and lower baseline fibrinogen levels in those subjects with CRP 40.33 mg/l. 32 The IL6 À174C4T polymorphism has been found to explain 14% of the baseline plasma CRP level.…”
Section: Introductionmentioning
confidence: 99%